Scalable feedback control for multicast video distribution in the Internet. - Bolot, Jean-Chrysostome
We describe a mechanism for scalable control of multicast continuous media streams. The mechanism uses a novel probing mechanism to solicit feedback information in a scalable manner and to estimate the number of receivers. In addition, it separates the congestion signal from the congestion control algorithm, so as to cope with heterogeneous networks.This mechanism has been implemented in the IVS video conference system using options within RTP to elicit information about the quality of the video delivered to the receivers. The H.261 coder of IVS then uses this information to adjust its output rate, the goal being to maximize the perceptual quality of the image received at the destinations while minimizing the bandwidth used by the video transmission. We find that our prototype control mechanism is well suited to the Internet environment. Furthermore, it prevents video sources from creating congestion in the Internet. Experiments are underway to investigate how the scalable proving mechanism can be used to facilitate multicast video distribution to large number of participants.
Keywords: Computer systems organization; Computer communication networks; Network architecture and design; Internet; Network communications; Special purpose and application based systems; Real time and embedded systems; Information systems; Information interfaces and presentation; Multimedia information systems; Video (e.g., tape, disk, DVI).; Algorithms; Design; Performance